Answer
Verified
431.1k+ views
Hint: We are asked to solve this question by simplification. So we can start from the left hand side and apply the laws of logic and reach the right hand side.
Formula used: Laws of logic:
(i) Idempotence: \[p\vee p\Leftrightarrow p,p\wedge p\Leftrightarrow p\]
(ii) Commutative: \[p\vee q\Leftrightarrow q\vee p,p\wedge q\Leftrightarrow q\wedge p\]
(iii) Associative: $(p\vee q)\vee r\Leftrightarrow p\vee (q\vee r),(p\wedge q)\wedge r\Leftrightarrow p\wedge (q\wedge r)$
(iv) Distributive: $p\vee (q\wedge r)\Leftrightarrow (p\vee q)\wedge (p\vee r),p\wedge (q\vee r)\Leftrightarrow (p\wedge q)\vee (p\wedge r)$
(vi) Absorption: $p\wedge 1\Leftrightarrow p,p\wedge 0\Leftrightarrow 0$
(vii) Dominance: $p\vee 1\Leftrightarrow 1,p\vee 0\Leftrightarrow p$
Here,$1$ denotes a statement which is always true (tautology) and $0$ denotes a statement which is always false (contradiction).
Complete step by step solution:
To prove left hand side equals right hand side we can start from left side.
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)$
By the associative property of logics we have,
(iii) Associative: $(p\vee q)\vee r\Leftrightarrow p\vee (q\vee r)$
Using this we can combine the first two terms.
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\wedge \neg q)\vee q]\vee (\neg p\wedge q)$
By the distributive property of logic we have,
(iv) Distributive: $p\vee (q\wedge r)\Leftrightarrow (p\vee q)\wedge (p\vee r)$
Using this result in the square bracket we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\vee q)\wedge (\neg q\vee q)]\vee (\neg p\wedge q)$
We know either a statement or its negation is always true.
$\Rightarrow \neg q\vee q\equiv 1$
Using this we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\vee q)\wedge 1]\vee (\neg p\wedge q)$
Then by absorption laws of logic we have,
(vi) Absorption: $p\wedge 1\Leftrightarrow p$
Using this result,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (p\vee q)\vee (\neg p\wedge q)$
Now again applying distributive laws we have,
(iv) Distributive: $p\vee (q\wedge r)\Leftrightarrow (p\vee q)\wedge (p\vee r),p\wedge (q\vee r)\Leftrightarrow (p\wedge q)\vee (p\wedge r)$
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\vee q)\vee \neg p]\wedge [(p\vee q)\vee q]$
By commutative property of logic we have,
(ii) Commutative: \[p\vee q\Leftrightarrow q\vee p\]
Using this we get,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(q\vee p)\vee \neg p]\wedge [(p\vee q)\vee q]$
Again using associative property,
(iii) Associative: \[\left( p\vee q \right)\vee r\Leftrightarrow p\vee \left( q\vee r \right)\]
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [q\vee (p\vee \neg p)]\wedge [(p\vee q)\vee q]$
We know either a statement or its negation is always true.
$\Rightarrow p\vee \neg p\equiv 1$
Using this we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (q\vee 1)\wedge [(p\vee q)\vee q]$
And applying associativity in the square bracket we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (q\vee 1)\wedge [p\vee (q\vee q)]$
For any statements we have
$q\vee q\equiv q\Rightarrow p\vee (q\vee q)=p\vee q$
Using this we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (q\vee 1)\wedge (p\vee q)$
By the laws of dominance we have,
(vii) Dominance: \[p\vee 1\Leftrightarrow 1\]
Using this we get,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv 1\wedge (p\vee q)$
Now again by laws of absorption,
(vi) Absorption: $p\wedge 1\Leftrightarrow p$
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv p\vee q$
So we had reached the right hand side.
$\therefore $ The result is proved.
Note: We can also prove this result with the help of truth tables.
But in the question it is said to use simplification. So we have to use this one. If not mentioned the method precisely we are free to use any one.
Formula used: Laws of logic:
(i) Idempotence: \[p\vee p\Leftrightarrow p,p\wedge p\Leftrightarrow p\]
(ii) Commutative: \[p\vee q\Leftrightarrow q\vee p,p\wedge q\Leftrightarrow q\wedge p\]
(iii) Associative: $(p\vee q)\vee r\Leftrightarrow p\vee (q\vee r),(p\wedge q)\wedge r\Leftrightarrow p\wedge (q\wedge r)$
(iv) Distributive: $p\vee (q\wedge r)\Leftrightarrow (p\vee q)\wedge (p\vee r),p\wedge (q\vee r)\Leftrightarrow (p\wedge q)\vee (p\wedge r)$
(vi) Absorption: $p\wedge 1\Leftrightarrow p,p\wedge 0\Leftrightarrow 0$
(vii) Dominance: $p\vee 1\Leftrightarrow 1,p\vee 0\Leftrightarrow p$
Here,$1$ denotes a statement which is always true (tautology) and $0$ denotes a statement which is always false (contradiction).
Complete step by step solution:
To prove left hand side equals right hand side we can start from left side.
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)$
By the associative property of logics we have,
(iii) Associative: $(p\vee q)\vee r\Leftrightarrow p\vee (q\vee r)$
Using this we can combine the first two terms.
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\wedge \neg q)\vee q]\vee (\neg p\wedge q)$
By the distributive property of logic we have,
(iv) Distributive: $p\vee (q\wedge r)\Leftrightarrow (p\vee q)\wedge (p\vee r)$
Using this result in the square bracket we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\vee q)\wedge (\neg q\vee q)]\vee (\neg p\wedge q)$
We know either a statement or its negation is always true.
$\Rightarrow \neg q\vee q\equiv 1$
Using this we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\vee q)\wedge 1]\vee (\neg p\wedge q)$
Then by absorption laws of logic we have,
(vi) Absorption: $p\wedge 1\Leftrightarrow p$
Using this result,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (p\vee q)\vee (\neg p\wedge q)$
Now again applying distributive laws we have,
(iv) Distributive: $p\vee (q\wedge r)\Leftrightarrow (p\vee q)\wedge (p\vee r),p\wedge (q\vee r)\Leftrightarrow (p\wedge q)\vee (p\wedge r)$
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(p\vee q)\vee \neg p]\wedge [(p\vee q)\vee q]$
By commutative property of logic we have,
(ii) Commutative: \[p\vee q\Leftrightarrow q\vee p\]
Using this we get,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [(q\vee p)\vee \neg p]\wedge [(p\vee q)\vee q]$
Again using associative property,
(iii) Associative: \[\left( p\vee q \right)\vee r\Leftrightarrow p\vee \left( q\vee r \right)\]
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv [q\vee (p\vee \neg p)]\wedge [(p\vee q)\vee q]$
We know either a statement or its negation is always true.
$\Rightarrow p\vee \neg p\equiv 1$
Using this we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (q\vee 1)\wedge [(p\vee q)\vee q]$
And applying associativity in the square bracket we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (q\vee 1)\wedge [p\vee (q\vee q)]$
For any statements we have
$q\vee q\equiv q\Rightarrow p\vee (q\vee q)=p\vee q$
Using this we have,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv (q\vee 1)\wedge (p\vee q)$
By the laws of dominance we have,
(vii) Dominance: \[p\vee 1\Leftrightarrow 1\]
Using this we get,
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv 1\wedge (p\vee q)$
Now again by laws of absorption,
(vi) Absorption: $p\wedge 1\Leftrightarrow p$
$(p\wedge \neg q)\vee q\vee (\neg p\wedge q)\equiv p\vee q$
So we had reached the right hand side.
$\therefore $ The result is proved.
Note: We can also prove this result with the help of truth tables.
\[p\] | \[q\] | \[\tilde{\ }p\] | \[p\to q\] | \[\tilde{\ }pVq\] |
\[T\] | \[T\] | \[F\] | \[T\] | \[T\] |
\[T\] | \[F\] | \[F\] | \[F\] | \[F\] |
\[F\] | \[T\] | \[T\] | \[T\] | \[T\] |
\[F\] | \[F\] | \[T\] | \[T\] | \[T\] |
But in the question it is said to use simplification. So we have to use this one. If not mentioned the method precisely we are free to use any one.
Recently Updated Pages
A wire of length L and radius r is clamped rigidly class 11 physics JEE_Main
The number of moles of KMnO4 that will be needed to class 11 chemistry JEE_Main
The oxidation process involves class 11 chemistry JEE_Main
A car starts from rest to cover a distance s The coefficient class 11 physics JEE_Main
The transalkenes are formed by the reduction of alkynes class 11 chemistry JEE_Main
At what temperature will the total KE of 03 mol of class 11 chemistry JEE_Main
Trending doubts
Which is the longest day and shortest night in the class 11 sst CBSE
Who was the Governor general of India at the time of class 11 social science CBSE
Why is steel more elastic than rubber class 11 physics CBSE
Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE
Define the term system surroundings open system closed class 11 chemistry CBSE
In a democracy the final decisionmaking power rests class 11 social science CBSE